Single-dose high-dose-rate brachytherapy compared to two and three fractions for locally advanced prostate cancer. Issue 1 (July 2017) - Hoskin, Peter; Rojas, Ana; Ostler, Peter; Hughes, Robert; Alonzi, Roberto; Lowe, Gerry
Abstract: Background: Single-dose high-dose-rate brachytherapy (HDR-BT), in a Phase-II study, was compared to two or three fractions in intermediate and high-risk localized prostate cancer. Patients and methods: 293 patients received 1 × 19 Gy or 1 × 20 Gy (A = 49), 2 × 13 Gy (B = 138), or 3 × 10.5 Gy (C = 106) and assessed with prospective measures of serum PSA, late genitourinary (GU) and gastrointestinal (GI) morbidity using RTOG scales and the International Prostate Symptom Score (IPSS). Results: Median follow-up is 49, 63 and 108 months (A, B and C, respectively). At 4 years biochemical relapse free survival was 94% (A), 93% (B) and 91% (C) ( p  = 0.54). Risk-category was the only significant independent predictor of relapse ( p  < 0.0001). Kaplan–Meier 4-year-estimates of GU-3 were 2% (A and B) and 11% (C). GI-3 was 0% (A and B) and 1% (C). No GU or GI grade-4 events were observed. IPSS ≥ 20 was 11% (A), 9% (B) and 16% (C) ( p  = 0.9). Prevalence of GU-3 was ≤4% in the 3 groups at all times; GI-3 was low or non-existent. Prevalence of catheter use was ≤6% in all groups. Conclusions: A single dose of 19–20 Gy achieves similar rates of late morbidity and biochemical control compared to 2 and 3 fractions.